Irritable bowel syndrome: expert guidance on diagnosis and management of challenging cases - Chaudhuri, Sujit (International Journal of Research in Medical Sciences, 2024)
Irritable bowel syndrome (IBS) is a common functional gastrointestinal condition that affects a large proportion of the world’s population. The diagnostic complications caused by the lack of unambiguous biomarkers, symptom overlap with other gastrointestinal illnesses, and heterogeneity within IBS subtypes are discussed. The article delves into the diverse pathophysiology of IBS and associated conditions such as small intestinal bacterial overgrowth (SIBO), mental disorders, and inflammatory bowel disease (IBD), highlighting the importance of the gut-brain axis and microbiome dysbiosis. Pain management options for IBS are discussed, including biofeedback therapy, dietary changes, antispasmodic medicines, and new therapies. Experts from India provided their recommendations on the need for a multidisciplinary approach towards management of IBS, with a view to achieving improvement in quality of life for individuals grappling with this complex disorder.